Association of Blood Pressure, BMI and Age among Adults above 18 Years of Makalbari Area of Gokarneswor Municipality in Kathmandu - Shrestha, SR; Shakya, B; Oli, R (Nepal Medical College Journal, 2019)
In Nepal the prevalence of hypertension is in increasing trend with an increased number of deaths from heart disease and stroke. The morbidity and mortality from hypertension, cardiovascular disease and other chronic diseases has been associated with high Body mass index (BMI). The current study aimed to study the association between BMI, blood pressure and age of the adults in Makalbari area. A community based cross-sectional study was conducted among 643 respondents. The information was obtained using self constructed structured questionnaire which included demographic information of individuals. Height, weight and blood pressure were recorded and hypertension was defined as per Joint National Committee (JNC) VII guidelines. Maximum value of mean BMI was found among 40– 49 years age group. BMI was found to be lowest among younger age group. Both the mean systolic and diastolic BP were found to be lowest among the youngest age groups. Mean Systolic BP increased steadily with age and the highest value was found among the oldest age group. Mean Diastolic BP increased with age till 40–49 years and declined thereafter. There was significant (P <0.01) positive correlation of BMI with systolic and diastolic BP. It showed that BP increased with increase in BMI. Correlation coefficient showed that relationship of BMI with systolic BP (0.231) was stronger than diastolic BP (0.167). Thus the present study provides valuable information regarding the association of BMI with systolic and diastolic blood pressure. It also showed the correlation of blood pressure with increasing age independently.